Cs2CO3-Promoted C(sp2)–N Formation of Dimethyl Thiocarbamate-Protected Indoles Using Tetramethylthiuram Monosulfide (TMTM) - Peng, Han-Ying; Wu, Yu-Xi; Dong, Zhi-Bing (Synthesis, 2020)
An efficient and simple synthesis of 1-thiocarbamoylindoles is reported in which 1H-indoles react with tetramethylthiuram monosulfide (TMTM) to give a series of 1-thiocarbamoylindoles that were obtained in good to excellent yields. The procedure was promoted by Cs2CO3 under transition-metal-free conditions and gives a simple entry to protected indoles.
Keywords: 1H-indole; thiuram; transition-metal-free; synthesis; 1-thiocarbamoylindole